2022
DOI: 10.1016/j.clcc.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intestinal Microbiota in Metastatic Colorectal Cancer Patients Treated With Capecitabine

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Furthermore, it has been indicated that Fusobacterium nucleatum might be able to induce chemoresistance to 5-FU in CRC cells, while Lactiplantibacillus (previously Lactobacillus) plantarum-derived supernatant seemed to sensitize CRC cells to the anticancer effects of 5-FU [24][25][26]. In contrast to this, our research group did not detect consistent capecitabine-induced changes in gut microbiota composition and diversity in a relatively small and heterogeneous group of CRC patients [27]. Other clinical studies, using different chemotherapeutics, described that chemotherapy treatment affected gut microbiota composition and the abundance of prominent SCFA-producing bacteria such as Veillonella and Prevotella [14,28,29].…”
Section: Introductioncontrasting
confidence: 94%
“…Furthermore, it has been indicated that Fusobacterium nucleatum might be able to induce chemoresistance to 5-FU in CRC cells, while Lactiplantibacillus (previously Lactobacillus) plantarum-derived supernatant seemed to sensitize CRC cells to the anticancer effects of 5-FU [24][25][26]. In contrast to this, our research group did not detect consistent capecitabine-induced changes in gut microbiota composition and diversity in a relatively small and heterogeneous group of CRC patients [27]. Other clinical studies, using different chemotherapeutics, described that chemotherapy treatment affected gut microbiota composition and the abundance of prominent SCFA-producing bacteria such as Veillonella and Prevotella [14,28,29].…”
Section: Introductioncontrasting
confidence: 94%
“…However, evidence from clinical studies in this eld of research is scarce. Previously, our research group did not detect capecitabine-induced changes in gut microbiota composition and diversity in a relatively small and heterogeneous group of CRC patients (27). Other clinical studies, using different chemotherapeutics, described that chemotherapy treatment affected gut microbiota composition and the abundance of prominent SCFA-producing bacteria such as Veillonella and Prevotella (14,28,29).…”
Section: Introductionmentioning
confidence: 70%
“…Analysis of the gut microbiota was performed as previously described (27). In short, metagenomic DNA from fecal samples was isolated using the Ambion MagMax™ Total Nucleic Acid Isolation Kit (Thermo Fisher Scienti c).…”
Section: Analysis Of Gut Microbiota Composition and Bacterial Abundancesmentioning
confidence: 99%
“…Metabolites produced by a healthy gut microbiota, such as short-chain fatty acids (e.g., acetic, propionic, and butyric acids), play important roles in maintaining the intestinal barrier, ( 43 ) providing energy ( 44 ) and immune homeostasis ( 45 ). It is well-recognized that gut microbiota also participate in modulating the intestinal microenvironment and host metabolism, while the gut microecology is vulnerable to the effects of unhealthy diet ( 46 ) and antibiotic treatments ( 47 ). Furthermore, the disruption of gut microbial homeostasis may result in metabolic shifts, ultimately leading to the pathological development of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%